A new species of Agapophyta Guérin-Meneville, 1828 from the Tanimbar Islands, Indonesia (Hemiptera : Heteroptera: Tessaratomidae: Oncomerinae) - Magnien, Philippe; Jindra, Zdeněk (Zootaxa, 2018)
A new species of Agapophyta Guérin-Méneville, 1831 (Hemiptera: Heteroptera: Tessaratomidae: Oncomerinae), Agapophyta kmenti sp. nov., is described from the Tanimbar Islands, Indonesia, male and female genitalia are illustrated. The new species is close to Agapophyta aurantiaca Blöte, 1945 and A. boschmai Blöte, 1945. A table of diagnostic characters is given to separate the three species.